Karakteristik Fruit Leather Buah Pala (Myristica fragrans) Dengan Variasi Jenis Hidrokoloid Gel - Dzakiah, Dzakiah; Imelda, Fenny; Saniah, Saniah; Narsih, Narsih (Politeknik Negeri Lhokseumawe, 2023)
Fruit leather is a processed food product from pulp of fruit flesh that has been crushed with the addition of stabilizer then dried in a mold using an oven, so as to form a thin sheet that can be rolled up. The raw material for fruit leather can come from fruits such as nutmeg flesh. The purpose of this study was to determine the physical and chemical characteristics of fruit leather from nutmeg flesh with a variation of 0.3% hydrocolloid gel (CMC, pectin and carrageenan). Parameters observed included color, texture, water content, and pH. The results showed that the physical characteristics of the fruit leather of nutmeg flesh with the addition of carrageenan had a texture value of 0.12 kg/mm2 and a color with an *L value of 27.45; the value of *a is 6.03; the value of *b is 13.20. While the chemical characteristics have a water content value of 22.37% and a pH of 3.56. The addition of CMC has a texture value of 0.28 kg/mm2 and a color value with a *L value of 30.78; the value of *a is 5.94; the value of *b is 12.41. While the chemical characteristics have a water content value of 19.03% and a pH of 3.51. The addition of pectin has a texture value of 0.23 kg/mm2 and a color value of *L, which is 31.02; the value of *a is 5.77; the value of *b is 12.31. While the chemical characteristics have a water content value of 16.61% and a pH of 3.33.